Pulmonary arteriovenous extracorporeal membrane oxygenation to avoid pulmonary overflow during total artificial heart implantation. Issue 1 (January 2018) - Tchantchaleishvili, Vakhtang; Luc, Jessica G.Y.; Sagebin, Fabio; Wong, Joshua K.; Massey, Howard T.
Total artificial hearts (TAH) can be used as a bridge to transplant or, occasionally, as destination therapy for patients with severe biventricular dysfunction. Not infrequently TAHs are placed in patients with severe low flow states, in which the lungs of these patients are unable to adjust rapidly to the "normal" right ventricular output of a TAH. These patients may develop variable degrees of pulmonary edema secondary to stress failure of the pulmonary capillaries requiring increased respiratory support, which can occasionally be fatal. In this "how to do it" article, we describe the technique for a pulmonary arteriovenous extracorporeal membrane oxygenation with TAH to avoid sudden pulmonary overflow and gradually expose the lungs to increasing flow.